The Palace of Palermo, River Plate’S Versalles: Soft Power and Heritage in the Times of Rosas and Sarmiento; [O Palácio de Palermo, Versailles del Plata: Soft Power E Património Nos Tempos de Rosas E Sarmiento]; [el Palacio de Palermo, Versalles del Plata: Poder Blando y Patrimonio en Tiempos de Rosas y Sarmiento] - Lacoste, P (Editora Universitaria da PUCRS, 2025)
During the argentine civil and foreign wars in the 1830s and 1840s, this article examines the mestizo cultural and agro-food heritage promoted by Juan Manuel de Rosas as a strategy of soft power. The role of the Palermo palace as a space of cohesion and national unity is highlighted, along with the enhancement of heritage architecture, utensils, food and drink. © 2025, Editora Universitaria da PUCRS. All rights reserved.